2018
DOI: 10.1186/s40168-018-0597-y
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosheath microbial community assembly of sympatric desert speargrasses is independent of the plant host

Abstract: BackgroundThe rhizosheath-root system is an adaptive trait of sandy-desert speargrasses in response to unfavourable moisture and nutritional conditions. Under the deserts’ polyextreme conditions, plants interact with edaphic microorganisms that positively affect their fitness and resistance. However, the trophic simplicity and environmental harshness of desert ecosystems have previously been shown to strongly influence soil microbial community assembly. We hypothesize that sand-driven ecological filtering cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 84 publications
4
80
0
Order By: Relevance
“…The other two clusters appeared much more site-specific and were dominant. This general picture of the organization and distribution of microbial consortia highlights the strong effect of the desert habitat over the soil-and rhizosphere-microbiome, coherently with Marasco et al (2018). However, the bacterial cluster appears to be consistently associated to C. longiscapa: the site-independent enrichment of this cluster in the rhizosphere further supports this conclusion.…”
Section: Co-occurrence Networksupporting
confidence: 54%
See 1 more Smart Citation
“…The other two clusters appeared much more site-specific and were dominant. This general picture of the organization and distribution of microbial consortia highlights the strong effect of the desert habitat over the soil-and rhizosphere-microbiome, coherently with Marasco et al (2018). However, the bacterial cluster appears to be consistently associated to C. longiscapa: the site-independent enrichment of this cluster in the rhizosphere further supports this conclusion.…”
Section: Co-occurrence Networksupporting
confidence: 54%
“…During the rainy year, C. longiscapa recruits and selects through sugar-rich exudates, amino acids and organic acids specific microorganisms (Marasco et al, 2018), which could favor its development under different aridity conditions, in addition to repel others. Consistent with previous studies of arid environments, Ascomycota (fungi), Proteobacteria and Bacteroidetes (prokaryotes) were the most abundant phylum in the active rhizosphere (Maestre et al, 2015;Hassani et al, 2018).…”
Section: Microbiome Dynamics Between a Rainy And A Dry Yearmentioning
confidence: 99%
“…However, previous reports show a larger diversity in rhizospheres than in soils comparing different biomes ( Thompson et al, 2017 ). Marasco et al (2018) found a higher 16S rRNA copies (qPCR) in the rhizosphere and rhizosheath than soil, of three species of dune colonizing speargrasses ( Stipagrostis sabulicola, S. seelyae, and Cladoraphis spinosa ). The larger rhizosphere and rhizoheath suggest an increase in microbial abundance and activity in these plants influenced microniches compared to soils.…”
Section: Resultsmentioning
confidence: 93%
“…Mantel test was used to analyse the correlation between two matrices, which were the dissimilarity matrix of bacterial communities (Bray-Curtis) and the distance matrix of tree ages. The occurrence of increasing delta tree age patterns in all 3 compartments has been tested using the linear regression between the dissimilarity of bacterial communities (Bray-Curtis) and the tree age differences (25), see supplementary table 3 and 4.…”
Section: Bacterial Diversity Abundance Distribution and Statistical mentioning
confidence: 99%